Influence of Temperature and Plant Growth Stages of Red Clover and Wheat on Small Broomrape (Orobanche minor) Germination. (March 2014) - Al-Thahabi, Salam A.; Colquhoun, Jed B.; Mallory-Smith, Carol A.
Abstract : Small broomrape is a holoparasitic plant that attaches to the roots of red clover as well as several other host plants. Hosts and false hosts produce stimulants that induce small broomrape germination but small broomrape does not attach to a false host. Wheat has been identified as a false host for small broomrape; therefore, studies were conducted to investigate the effect of red clover and wheat root exudates on small broomrape germination. In one study, the effect of exudates from red clover and wheat at multiple growth stages on small broomrape germination was evaluated. Red clover induced small broomrape germination at all growth stages tested but was greatest (78%) in the presence of exudates from red clover at the three-trifoliolate stage. Maximum small broomrape germination was 25% when exposed to exudates produced by one-leaf-stage wheat. In a second study, the relationship between small broomrape germination and host growth condition was evaluated using root exudates from red clover or wheat grown under several temperature conditions for either 4 or 8 wk. For the different temperatures, there were no differences in small broomrape germination when exudates of red clover grown for 4 wk were used. Small broomrape germination was reduced when exposed to exudates from red clover plants grown for 8 wk at 10 C compared with plants grown at 15, 20, and 25 C. Differences in small broomrape seed germination were observed with temperature under which wheat was grown for 4 wk, but not for 8 wk. Although wheat exudates resulted in less small broomrape seed germination than red clover exudates, growing wheat as a false host in a small broomrape-infested field could be an important component of an integrated management plan.